Structural and Biomolecular Analyses of Borrelia burgdorferi BmpD Reveal a Substrate-Binding Protein of an ABC-Type Nucleoside Transporter Family - Cuellar J; Åstrand M; Elovaara H; Pietikäinen A; Sirén S; Liljeblad A; Guédez G; Salminen TA; Hytönen J (American Society for Microgiology, 2022)
Borrelia burgdorferisensu lato, the causative agent of tick-borne Lyme borreliosis (LB), has a limited metabolic capacity and needs to acquire nutrients, such as amino acids, fatty acids, and nucleic acids, from the host environment. Using X-ray crystallography, liquid chromatography-mass spectrometry, microscale thermophoresis, and cellular localization studies, we show that basic membrane protein D (BmpD) is a periplasmic substrate-binding protein of an ABC transporter system binding to purine nucleosides. Nucleosides are essential for bacterial survival in the host organism, and these studies suggest a key role for BmpD in the purine salvage pathway of B. burgdorferi sensu lato Because B. burgdorferisensu lato lacks the enzymes required for de novo purine synthesis, BmpD may play a vital role in ensuring access to the purines needed to sustain an infection in the host. Furthermore, we show that, although human LB patients develop anti-BmpD antibodies, immunization of mice with BmpD does not confer protection against B. burgdorferi sensu lato infection.